2004
DOI: 10.1111/j.1348-0421.2004.tb03490.x
|View full text |Cite
|
Sign up to set email alerts
|

New Lactococcus Strain with Immunomodulatory Activity: Enhancement of Th1‐Type Immune Response

Abstract: Few studies exist dealing with the probiotic activity of lactococci, which are commonly used as starter bacteria in the manufacture of many kinds of fermented dairy products. Fifteen strains of the genus Lactococcus were examined for their probiotic activities, such as immunomodulatory effects. Six strains induced the production of cytokines (IL-12, IL-6, and TNF-␣) in macrophage-like cell line J774.1, and the highest induction was observed with Lactococcus lactis subsp. lactis G50. The cytokine induction in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
72
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 24 publications
5
72
0
3
Order By: Relevance
“…Probiotic bacteria of Lactococcus lactis subsp. lactis G50 was stated to increase cytokines related with Th1 and showed anti-inflammatory effect by suppressing the hypersensitivity reactions (Kimoto et al 2004). We found that IL-6 levels were significantly decreased in the probiotic, exercise, and restriction subgroups of both young and old groups.…”
Section: Discussionmentioning
confidence: 66%
“…Probiotic bacteria of Lactococcus lactis subsp. lactis G50 was stated to increase cytokines related with Th1 and showed anti-inflammatory effect by suppressing the hypersensitivity reactions (Kimoto et al 2004). We found that IL-6 levels were significantly decreased in the probiotic, exercise, and restriction subgroups of both young and old groups.…”
Section: Discussionmentioning
confidence: 66%
“…Lactis G50 killed by heat to induce cytokine production of macrophages in culture, was previously proved by Kimoto et al (2004), it was observed that this strain continued to induce cytokine production, suggesting that such activity is associated with elements on the bacterial wall. Ghadimi et al (2008) proved that Lactobacillus rhamnosus GG, Lactobacillus gasseri (PA16/8), Bifidobacterium bifidum (MP20/5) and Bifidobacterium longum (SP07/3), as well as their genomic DNA, dosedependently modulated the TH1/TH2 response to allergens.…”
Section: Discussionmentioning
confidence: 71%
“…Lactococcus strain G50 described above did not produce slime products. Induction of cytokine production in clonal macrophage by the heatkilled cells of strain G50 was observed 19 , indicating that it is not critical whether cells are viable or nonviable (heatkilled) for the immunomodulatory effects of strain G50 although strain G50 was proved to reach the intestine alive by using mice (unpublished data). In strain G50, cell wall components, which constitute heat-killed cells, may be a factor for immune modulation by this strain.…”
Section: Immune Modulationmentioning
confidence: 99%